Clinical Presentation of Irritable Bowel Syndrome and Related Quality of Life among Cameroonian Medical Students: A Cross-Sectional Descriptive Study - Ndam Antonin Wilson Ndjitoyap; Tenone Danah; Leuwat Eric Pascal Tchoumi; Domissek Desire Bakelak; Paul Talla; Andoulo Firmin Ankouane; Ndam Elie Claude Ndjitoyap; Oudou Njoya; Mathurin Pierre Kowo (European Scientific Journal, ESJ, 2026)
Background: Irritable Bowel Syndrome (IBS) is a functional gastrointestinal disorder characterized by chronic abdominal pain and altered bowel habits without structural abnormalities. Though non-lethal, it significantly affects the quality of life of sufferers. In Sub-Saharan Africa, data on IBS are limited. Objective: Describe the clinical presentation of IBS and the quality of life among medical students in our country. Methods: A descriptive cross-sectional prospective study was conducted in two medical schools. Stratified sampling was employed to recruit a total of 260 students. Data gathered included sociodemographic details, Rome IV diagnostic criteria, Bristol stool scale scores, gastrointestinal symptoms, and quality-of-life predictors. Statistical analysis was done using IBM SPSS version 26. Results: Out of the 260 students, the prevalence of presumed IBS was 11.2%. IBS-C was most common (41.4%), followed by IBS-D (31%), IBS-M (20.7%), and unclassified (6.9%). IBS-C was significantly associated with females (p = 0.021, Cramer's V = 0.412), irregular meals (p = 0.013, Cramer's V = 0.519), and morning predominance of pain (p = 0.011, Cramer's V = 0.508). The triad: defecation-related abdominal pain, altered stool consistency, and altered stool frequency was present in 68.9% of students with IBS. Most students with IBS reported diffuse (62.1%), persistent (34.5%) abdominal pain with mixed triggers and relieving factors. Quality of life was altered in 58.6% of students with IBS, with 10.3% experiencing severe impairment. Conclusion: Presumed IBS among medical students in our study was non-negligible, with a predominance of IBS-C. Clinical profile was dominated by diffuse, persistent abdominal pain with multiple triggers. Quality of life was altered in most students with IBS.